Improved singular value inclusion sets for rectangular tensors - Jun He; Yanmin Liu (Journal of Inequalities and Applications, 2025)
Abstract In this paper, improved singular value inclusion sets for rectangular tensors are given, which are tighter than those in (Zhao and Li in Linear Multilinear Algebra 66(7):1333–1350, 2018). Numerical experiments are reported to show the efficiency of the given inclusion sets.